Automatic target detection using wavelet technique in forward scattering radar - Mohamed, Mohamed Khalaf Alla Hassan; Cherniakov, Mike; A. Rasid, Mohd Fadlee; Raja Abdullah, Raja Syamsul Azmir (IEEE, 2008)
This paper describes aspects of ground target detection in forward scattering radar (FSR). The problem of extracting the Doppler signature in different interference environments is addressed. Hilbert transform and wavelet technique have been used to predict the existence of target. The paper begins with a brief description of the system, followed by a more detailed analytical study of predicting the presence of target in FSR. Two sets of practical experimentation have been realised to evaluate the proposed algorithm.